PENCIPTAAN TEATER KOMUNITAS: ECODRAMATURGI DAN PENGETAHUAN LOKAL PACITAN - Indrata Nur Bayuaji; Eko Supriyanto; Suroto Suroto (JURNAL PAKARENA, 2025)
This article explains community theatre creation in Pacitan based on Resik Kali, Thethek Melek, and Entas-Entas. It employs practice as research and autoethnography through participant observation, interviews, artistic exploration, and collaboration with villagers. The findings show that Pacitan’s agrarian rituals form a socio-ecological dramaturgical structure of environmental care, crop protection, communal solidarity, and food redistribution. It concludes that local tradition in community theatre creation functions as a source of artistic, ecological, and social knowledge for contemporary theatre-making.